2015
DOI: 10.1063/1.4919321
|View full text |Cite
|
Sign up to set email alerts
|

NiCo-lead zirconium titanate-NiCo trilayered magnetoelectric composites prepared by electroless deposition

Abstract: The NiCo layers with various Ni/Co atomic ratio have been successfully electroless deposited on PZT layers by varying the bath composition. As the cobalt atomic ratio in the deposited layer increases from 17.2 to 54.8 wt%, the magnetostrictive coefficient decreases. The magnetoelectric effect depends strongly on the magnetostrictive properties of magnetostrictive phase. The magnetoelectric coefficient of NiCo/PZT/NiCo trilayers increases with Ni/Co atomic ratio of the deposited NiCo layers increasing from 45:5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In addition to the self-biased behavior in graded composite, it was observed that FeCo/Ni/ PZT/Ni/FeCo and Ni/PZT/Ni yielded the best quasi-static and resonant responses, respectively. In a later development, the effect of Co content in NiCo magnetostrictive layer was studied, wherein the composition of FeCo was changed by varying the bath composition [142]. It was inferred that maximum ME response improves significantly from 100 to 330 mV cm −1 Oe when Co content in NiCo decreases from 55% to 17%.…”
Section: Electroless Deposition Methodsmentioning
confidence: 99%
“…In addition to the self-biased behavior in graded composite, it was observed that FeCo/Ni/ PZT/Ni/FeCo and Ni/PZT/Ni yielded the best quasi-static and resonant responses, respectively. In a later development, the effect of Co content in NiCo magnetostrictive layer was studied, wherein the composition of FeCo was changed by varying the bath composition [142]. It was inferred that maximum ME response improves significantly from 100 to 330 mV cm −1 Oe when Co content in NiCo decreases from 55% to 17%.…”
Section: Electroless Deposition Methodsmentioning
confidence: 99%